2017
DOI: 10.3171/2015.6.jns15311
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline for uncoilable or failed aneurysms: 3-year follow-up results

Abstract: OBJECTIVE The long-term effectiveness of endovascular treatment of large and giant wide-neck aneurysms using traditional endovascular techniques has been disappointing, with high recanalization and re-treatment rates. Flow diversion with the Pipeline Embolization Device (PED) has been recently used as a stand-alone therapy for complex aneurysms, showing significant improvement in effectiveness while demonstrating a similar safety profile to stent-supported coil treatment. However, relatively little is known ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(112 citation statements)
references
References 48 publications
4
105
1
2
Order By: Relevance
“…In the Pipeline for Uncoilable or Failed Aneurysms (PUFS) trial, the rate of completely occluded aneurysms at 1 year was 86.8% 1 and climbed to 93.4% at 3 years and 95.2% at 5 years. 16,17 Aneurysms in PUFS, however, were notably larger at a median aneurysm diameter of 17.5 mm compared with 7.6 mm in the EuFRED. Aneurysms of Ͼ20 mm were also associated with a lower rate of occlusion in the EuFRED.…”
Section: Aneurysm Occlusion After Fredmentioning
confidence: 97%
“…In the Pipeline for Uncoilable or Failed Aneurysms (PUFS) trial, the rate of completely occluded aneurysms at 1 year was 86.8% 1 and climbed to 93.4% at 3 years and 95.2% at 5 years. 16,17 Aneurysms in PUFS, however, were notably larger at a median aneurysm diameter of 17.5 mm compared with 7.6 mm in the EuFRED. Aneurysms of Ͼ20 mm were also associated with a lower rate of occlusion in the EuFRED.…”
Section: Aneurysm Occlusion After Fredmentioning
confidence: 97%
“…When evaluating the 3-year follow-up results for the Pipeline for Uncoilable or Failed Aneurysms (PUFS) trial, the investigators found that 15 patients had a residual aneurysm or residual neck. Four of these patients underwent further treatment with a second PED (Table 3), 3 and 2 (50%) of these 4 progressed to complete occlusion. The 2 patients treated with PEDs at our institution following failed flow diversion each presented with large fusiform aneurysms of the ICA, requiring multiple stents during their first and second treatments.…”
Section: Ped Following Failed Flow Diversionmentioning
confidence: 99%
“…Given that the PED is still in its infancy, little literature exists regarding PED failures and treatment options for recurrent aneurysms following prior PED apart from a few case reports. 3,7,15 In a study evaluating the treatment of 119 unruptured aneurysms with a PED, 7 patients experienced occlusion failure, and in 3 of the 7 cases, this residual was treated with a second PED. 7 Unfortunately, adequate follow-up to assess the durability of this second treatment was not available.…”
Section: Ped Following Failed Flow Diversionmentioning
confidence: 99%
“…Conversely, the PUFs trial demonstrated that flow diversion for giant ICA aneurysms is a safer alternative (93% occlusion rate, 5% mortality rate), with many aneurysms that were incompletely occluded initially becoming completely occluded over time 5 6. Endoluminal reconstruction of the diseased segment leads to aneurysm occlusion and anatomical resolution of the mass effect over time with low rates of complications (6% of major stroke or death) 6. The procedure is performed relatively quickly, and most patients are discharged home the following day.…”
Section: Illustrative Case Scenariosmentioning
confidence: 99%
“…In contrast to the high occlusion rate when flow diversion is performed as an initial treatment (93%),6 flow diversion for recurrent aneurysms is less effective 40. Daou et al found that if a stent is already present, flow diversion for a recurrent aneurysm had an occlusion rate of 56%, with 10% of cases requiring retreatment 40.…”
Section: Illustrative Case Scenariosmentioning
confidence: 99%